1991
DOI: 10.1104/pp.97.3.1059
|View full text |Cite
|
Sign up to set email alerts
|

Hydroperoxide Lyase and Other Hydroperoxide-Metabolizing Activity in Tissues of Soybean, Glycine max

Abstract: Hydroperoxide lyase (HPLS) activity in soybean (Glycine max) seed/seedlings, leaves, and chloroplasts of leaves required detergent solubilization for maximum in vitro activity. On a per milligram of protein basis, more HPLS activity was found in leaves, especially chloroplasts, than in seeds or seedlings. The total yield of hexanal from 13(S)-hydroperoxy-cis-9,trans-1 1-octadecadienoic acid (13S-HPOD) from leaf or chloroplast preparations was 58 and 66 to 85%, respectively. Because of significant competing hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
70
2

Year Published

1992
1992
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(73 citation statements)
references
References 27 publications
1
70
2
Order By: Relevance
“…A good example of apparent LAH limitation to C6-aldehyde formation is found in mature soybean seeds. The addition of FFA substrates greatly increases C6-aldehyde formation by soybean seed meal (23) and seed extracts (8). In our current work, although the limiting action of LAH was not directly investigated, the possibility cannot be excluded with the young leaves.…”
Section: Discussionmentioning
confidence: 72%
See 4 more Smart Citations
“…A good example of apparent LAH limitation to C6-aldehyde formation is found in mature soybean seeds. The addition of FFA substrates greatly increases C6-aldehyde formation by soybean seed meal (23) and seed extracts (8). In our current work, although the limiting action of LAH was not directly investigated, the possibility cannot be excluded with the young leaves.…”
Section: Discussionmentioning
confidence: 72%
“…Results showed that in soybean leaves (regardless of age), there was little difference in LOX activity with 18:2 or 18:3, but based on spectrophotometric analyses, HPL preferentially utilized 13-HPOT, although C6-aldehyde formation was far higher in the presence of 13-HPOD than in the presence of 13-HPOT (Table I) a These results are apparently underestimated because of a comparatively lower partition of trans-2-hexenal and cis-3-hexenal from aqueous solution into headspace and rapid depletion of cis-3-hexenal at longer times (8).…”
Section: C6-aldehyde Formation By Lox and Hplmentioning
confidence: 63%
See 3 more Smart Citations